Cooperation rather than competition in industrial organisations: Albion W. Small's underestimated view. Issue 3 (3rd April 2017) - Vallet, Guillaume
Abstract: This article aims to present Albion W. Small's underestimated view on labour relations in industrial organisations. A century ago, this sociologist, who also had a grounding in political economy, analysed the transformation of capitalism through a focus on the relationship between workers and capitalists. He offered some interesting proposals, stressing the need for the two factors of production to cooperate instead of competing. His approach may still be insightful today in rethinking the forthcoming challenges facing industrial organisations as well as capitalism, especially regarding the ontological nature of a firm associated with its governance issue.